2019
DOI: 10.1371/journal.pone.0213240
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of hypertensive disorders in pregnancy at a referral hospital, Southern Ethiopia

Abstract: Introduction Hypertensive Disorders in Pregnancy (HDP) complicate about 10% of pregnancies. It accounts to 50% of maternal death in sub-Saharan Africa and precedes 15% of perinatal deaths worldwide. In this study, we looked at the perinatal outcomes and factors associated with unfavorable perinatal outcomes among women with hypertensive disorders in pregnancy at Wolaita Sodo teaching and referral hospital, southern Ethiopia. Methods A hospital based retrospective cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
(34 reference statements)
7
24
0
Order By: Relevance
“…In this study, approximately one-third (28.8%) of the newborns delivered from women with PIH were admitted to the neonatal intensive care unit (NICU). This finding was consistent with the study conducted in Uganda (32.1%) and Ghana (24.7%) (21,47) but higher than a study conducted in Iran (13%) (31). The higher risk of newborn baby admission to NICU might be related to the effect of PIH on low birth weight, birth asphyxia, and preterm births.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, approximately one-third (28.8%) of the newborns delivered from women with PIH were admitted to the neonatal intensive care unit (NICU). This finding was consistent with the study conducted in Uganda (32.1%) and Ghana (24.7%) (21,47) but higher than a study conducted in Iran (13%) (31). The higher risk of newborn baby admission to NICU might be related to the effect of PIH on low birth weight, birth asphyxia, and preterm births.…”
Section: Discussionsupporting
confidence: 92%
“…To date, most studies examining maternal and perinatal outcomes in women with HDP from sub-Saharan Africa have been limited to retrospective and cross-sectional data [7][8][9][10][11][12][13][14][15][16][17]. Additionally most studies from sub-Saharan Africa are from institutions based in large urban and metropolitan areas, thus data is lacking on outcomes among women with HDP seeking care in more rural and agrarian settings [9,12,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Existing data suggest an increased risk of maternal and perinatal adverse outcomes in women with HDP compared to women without HDP [15,17,19,20]. Several demographic (age, education, rural domicile), medical (pre-existing hypertension, multiparity, gestational age at delivery) and management (timing of drug administration) characteristics have been identified as risk factors for adverse perinatal and maternal outcomes among women with HDP [9- 11,14,15,[21][22][23]. However, it is unknown if similar rates of adverse outcomes and risk factors persist in a mostly rural population.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, several individual studies were done and reported inconsistent findings in the relationship between PIH and LBW, except one review published in 2019 which didn't include all currently available researches on association of PIH and LBW (studies done after the previous review) [30]. Accordingly, the prevalence of LBW among PIH women ranges from 9.8% [31] to 64.4% [32]. In addition, the odds of developing LBW among women who had PIH range from 1.31 to 10.33 [20,33].…”
Section: Introductionmentioning
confidence: 99%